Cycles inside cycles: Spanish regional aggregation - Ana Gomez Loscos; M. Dolores Gadea; Antonio Monta\~nes (European Regional Science Association (ERSA), 2011)
This paper sets out a comprehensive framework to identify regional business cycles within Spain and analyses their stylised features and the degree of synchronization present among them and the Spanish economy. We show that the regional cycles are quite heterogeneous although they display some degree of synchronization that can be partially explained using macroeconomic variables. We also propose a dynamic factor model to cluster the regional comovements and \~A-nd out if the country cycle is simply the aggregation of the regional ones. We \~A-nd that the Spanish business cycle is not shared by the seventeen regions, but is the sum of the diÂerent regional behaviours. The implications derived from our results are useful both for policy makers and analysts.
Keywords: 330